1) F(x) = 4x - x^3/3 + C
F(-3) = 4(-3) - (-3)^3/3 + C = -12 + 27/3 + C = -3 + C = 10
C = 13
F(x) = 4x - x^3/3 + 13
2) f(x) = F'(x) = (cos 3x - cos pi)' = -3sin 3x
3) F(x) = -3/x - 7/5*sin 5x + C
4) Найдем, где они пересекаются - это пределы интегрирования
y = x^2
y = 6 - x
x^2 = 6 - x
x^2 + x - 6 = 0
(x + 3)(x - 2) = 0
Int(-3; 2) (6 - x - x^2) dx = 6x - x^2/2 - x^3/3 | (-3; 2) =
= 6*2 - 2^2/2 - 2^3/3 - (6(-3) - (-3)^2/2 - (-3)^3/3) =
= 12 - 2 - 8/3 + 18 + 9/2 - 9 = 10 + 9 - 8/3 + 9/2 = 19 + 11/6 = 20 5/6
5) Найдем, где они пересекаются - это пределы интегрирования
2sin x = sin x
sin x = 0
x1 = 0; x2 = pi
Int(0; pi) (2sin x - sin x) dx = Int(0; pi) sin x dx = cos x |(0; pi) =
= |cos pi - cos 0| = |-1 - 1| = |-2| = 2
Подробнее - на -
ответ:
пошаговое объяснение:
а) -37,8: 3,6+12,5*(-0,6) = -18
-37,8: 3,6= -10.5
12,5*(-0,6) = -7.5
-10.5+(-7.5)= -18
б) (-17,15•0,6+19,98: (-5,4)): 0,1 = -139.9
-17,15•0,6= -10.29
19,98: (-5,4)= -3.7
-10.29+(-3.7)= -13.99
-13.99: 0.1= -139.9
в) (39,96: (-3,7)-14,25•0,8)•0,1= -2.22
39,96: (-3,7)= -10.8
14,25•0,8=11.4
-10.8-11.4= -22.2
-22.2*0.1= -2.22